Kinetic Study of Catalytic Hexane Isomerization - A.K. Mohammed, Abdul Halim; M. Rahman, Ameel; Al-Hassani, Maha (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
The isomerization of n-hexane on platinum loaded acidic zeolite was studied at atmospheric pressure, H2/nC6 molar ratios of 1-4 and temperature range of 240-270ºC. The measured kinetic data were fitted to an equation based on the bifunctional mechanism and by using independently obtained dehydrogenation and adsorption data. The activation energies of protonation (ΔHpro) and the elementary isomerization step (Eact,iso) and as well as the corresponding preexponential factor were simultaneously determined. The observed values of both ΔHpro and Eact,iso are in agreement with the results of quantum-chemical calculations.